THE EFFECTIVENESS OF DEMONSTRATION TECHNIQUE IN THE STUDENT’S SPEAKING ABILITY: A CASE STUDY OF THE EIGHT GRADE AT MADRASAH TSANAWIYAH NW DAMES IN THE SCHOOL YEAR 2018-2019 - Azhar (Scientia Integritas Utama, 2022)
This study aimed to investigate the effective of Demonstration Technique in teaching speaking skill for the students of the Eighth Grade of Madrasah Tsanawiyah NW Dames.This research used pre-experimental research with pre-test and post-test design. It was conducted at the Eighth Grade of Madrasah Tsanawiyah NW Dames in the school year 2018-2019. The sample consisted of 29 students selected by using random sampling. The data collected by using T- test. In descriptive statistic, the data analyzed by using paired sample T-test. The mean score of post-test (81.52) was higher than pre-test (34.07). The result of paired sample T-test indicated that there was a significant difference in the mean scores between pre-test and post-test, t(df=16) = 47.45 at p = 0.00. Based on the finding, it can be concluded that Demonstration Technique was significantly effective in teaching speaking at the Eighth Grades of Madrasah Tsanawiyah NW Dames